Not Just Solidarity Providers. Investigating the Political Dimension of Alternative Action Organisations (AAOs) during the Economic Crisis in Greece - Angelos Loukakis (Coordinamento SIBA, 2018)
The current economic crisis was a turning point, for the worse, in the everyday reality for a huge sector of the Greek population. Austerity-stricken Greece is characterised by the collapse of the wel-fare state and by increasingly uncovered basic needs. The answer to this humanitarian problem has been given by thousands of formal and informal initiatives and organisations and their solidarity actions, such as barter networks, food banks, consumers-producers networks, soup kitchens, new cooperatives, social economy enterprises and free legal advice. Despite the role of these initiatives and organisations in cover-ing needs, there are also signs that some of them make claims for social and/or political change. Conse-quently, some of these groups and organisations function in the political arena. This paper aims to map and analyse Alternative Action Organisations (AAOs), which are engaged with solidarity and political ac-tions, as well. It compares 'political AAOs' (engaged in protest, awareness raising and lobbying activities) and 'non-political AAOs' (engaged exclusively in solidarity actions) with respect to some of their main fea-tures. Moreover, the paper aims, through explanatory analysis, to uncover the predictors associated with AAOs' engagement in political activities.